Metacommunity structure of aquatic gastropods in a river floodplain: the role of niche breadth and drift propensity. (26th August 2013) - Funk, Andrea; Schiemer, Friedrich; Reckendorfer, Walter
Summary: Metacommunity ecology predicts the relative importance of environmental and spatial processes in the structure of species assemblages. Such processes may act differentially on subsets of the community characterised by specific traits. To gain a deeper insight into these mechanisms, we supplemented a common method of studying metacommunities with an analysis of individual species and their traits. River floodplains are challenging environments for metacommunity analysis due to their spatial heterogeneity, temporal stochasticity and configurations of the networks of waterbodies. An analysis of aquatic gastropods showed that both environmental and spatial factors had significant influence. Within the spatial variables tested, the configuration of the floodplain network upstream of a sampling site was particularly important. An analysis of individual species revealed that traits related to niche breadth and drift propensity were significant for structuring the assemblages: species with a broad niche width (i.e. generalist, or neutral species) and a high drift propensity were governed more by the spatial configuration, whereas environmental conditions mainly determined the distribution of specialists having traits that prevented drift. These results can be interpreted as a trade‐off between habitat specialisation and colonisation ability: specialists succeed locally due to competitiveness and a strategy of reducing risks by preventing drift, whereas generalists may succeed regionally due to a strategy of spreading risks, by high levels of reproductive output, dispersal rates and adaptability. Our findings have implications for schemes to restore river floodplains that affect the aquatic network, with subsequent effects on community assembly and thus on biodiversity.